Comparison Between Indirect Fluorescent Antibody Test and Modified Agglutination Test for Detecting Anti-Toxoplasma gondii IgG Antibodies in Neotropical Primates - Carvalho, Nycolas Octavio Ribeiro [UNESP]; Gaspar, Raquel Cuba [UNESP]; Lima, Suellen Gonçalves [UNESP]; da Silva Zanini, Dayane [UNESP]; Rodrigues, Nássarah Jabur Lot [UNESP]; Guimarães, Victor Yunes [UNESP]; da Silva, Aristeu Vieira; Rahal, Sheila Canevese [UNESP]; Henrique, Anna Luisa Pizzaia [UNESP]; Fornazari, Felipe [UNESP]; Langoni, Helio [UNESP] (Wiley, 2025)
Background: Toxoplasma gondii is a zoonotic parasite with a great impact on the health of Neotropical primates (NP). The aim of this study was to compare the agreement between the immunofluorescent antibody test (IFAT) and the modified agglutination test (MAT) to detect IgG anti-T. gondii antibodies in NP. Methods: Convenience serum samples of 77 animals were tested by IFAT and MAT according to standard protocols, and the agreement between results was analyzed using McNemar's χ2 test. Results: The samples included 30 red-handed howlers (Alouatta belzebul), 24 brown howler monkeys (Alouatta guariba), 22 capuchin monkeys (Sapajus nigritus), and one wedge-capped capuchin (Cebus olivaceous). Overall prevalence was 25.9% (n = 20), with three animals positive by IFAT and 20 positives by MAT. The agreement between tests was low (Kappa = 0.21). Conclusion: The results indicated that IFAT and MAT are not comparable to assess qualitatively anti-T. gondii IgG serum antibodies in the studied species.
Keywords: serology; toxoplasmosis; zoonosis